Arching behaviour of precast concrete slabs in a deconstructable composite bridge deck. (15th July 2015) - Valipour, H.; Rajabi, A.; Foster, S.J.; Bradford, M.A.
Highlights: A deconstructable steel–concrete composite bridge deck is proposed. Experimental data on arch behaviour of precast RC deck slabs are provided. Efficiency of cross-bracing and transverse ties for inducing arch action is studied. Application of bolted shear connectors in a deconstructable deck is studied. Abstract: This paper describes the results of the testing of precast concrete slabs in a deconstructable composite steel–concrete system for the construction of bridge decks. Benign arching action is utilised to carry the point (wheel) loads to the supports and to develop the required slab capacity; the failure mode and load–deflection response of the precast concrete slabs being investigated in the study. Twelve half-scale precast reinforced concrete slab strips were tested, with the slabs being attached to steel girders using friction grip bolts to provide shear connection between the deck and the supporting steel girders. The systems were tested under a monotonically increasing point load, which simulates vehicle wheel loading. The configuration and proportion of the reinforcing steel bars and the types of transverse cross-bracing and transverse straps were the main test variables. It is concluded that friction grip bolted shear connectors can prevent relative slip between the steel girders and concrete deck slabs, so that the equilibrating tension force in the cross-bracing/transverse straps, required to develop compressive arching in the slabs, can be developed. The arching effect in the slabs is very beneficial, and cannot be ignored in rational structural design processes.